Desafios educacionais criativos associados às práticas docentes : estudo de caso considerando RPG educacional - Pool, Mario Augusto Pires (2017)
This thesis, linked to the Graduate Program in Education of the School of Humanities of the Pontifical Catholic University of Rio Grande do Sul, included in the research line FOPPE (Training, Policies and Practices in Education), investigated how the leisure habits of teachers contribute to the creation of creative educational challenges, from the study of teachers who have created educational RPGs. It was investigated how the teacher who creates RPG games associates the contents of his discipline with his pedagogical practices linked to the challenges he proposes to his students. It was also sought to understand how the pedagogical practices created by these teachers are influenced by their being (a) a player. In order to understand the implications of leisure habits in teaching, it was necessary to verify how the formation of these teachers was constituted so that they could create such practices considering the structure of an RPG. Of the theoretical reference used, the following authors stand out: Bloom, Lévy, Carrano, Morin, Santaella, Amaral, Bergmann and Prensky. As a research methodology, a qualitative, case-study approach was adopted. As a method of data analysis, the Discursive Textual Analysis was adopted, the data collection instruments being a questionnaire and an interview. The subjects of this research were primary and secondary school teachers who created or adapted RPG games to be able to work the contents of their disciplines. As contributions of this thesis we propose a guide for the organization of pedagogical practices using RPG, elements for reflection on the possibility / necessity to revise the teaching protagonism, using as an articulating / transversal element its leisure habits, seeking to contribute to the discussions related to the formation of teachers . And, expand the scope of use of games, especially RPG type, as a pedagogical resource in the stages and training that go beyond the initial years. We understand that the playful and interdisciplinary aspect of this modality of play is strengthened in cyberculture.